The Relationship between Blood MDA Levels and Aortic Foam Cells in Menopausal Wistar Rats Treated with Cempaka Flower Extract - Lely firrahmawati; Endang Sri Wahyuni; M. Mulyaningsih; Prihani Sandra Widyanti (P3M Universitas 'Aisyiyah Surakarta, 2021)
Menopause is the natural end of the menstrual cycle which results in decreased estrogen (hypoestrogen) levels. The number of free radicals can increase due to decreased estrogen as a natural antioxidant in the body. The effect of increasing free radicals can be reduced by consuming antioxidants. Cempaka flower (Michelia champaca L) contains flavonoids which function as antioxidants. Materials and methods: proved a relationship between blood MDA levels and aortic foam cells in menopausal wistar rats treated with Cempaka flower extract. Research Methods: using experimental design with post test only control group design approach. The sample used 24 female rats (Rattus novergicus strain Wistar) with a menopausal age (450-540 days). Reasult: The normality assumption test with Saphiro Wilk obtained a p-value of 0.537 more than Î± = 0.05 (p> 0.05). The homogeneity test of variance with the Levene test obtained a p-value of 0.271 more than 0.05 (p> 0.05). Testing the effect of giving Cempaka flower extract on MDA levels using ANOVA obtained a p-value of 0.000 smaller than Î± = 0.05 (p <0.05). There was a significant difference in MDA levels due to the administration of cempaka flower extract at different doses. Testing the effect of giving Cempaka flower extract on the number of foam cells with the Kruskal-Wallis test obtained a p-value of 0.004, smaller than Î± = 0.05 (p <0.05). There is a significant difference in the number of foam cells due to the administration of Cempaka Flower extract with different doses. Testing the correlation between MDA levels and the number of foam cells used the Spearman correlation test with a correlation coefficient of 0.380 and a p-value of 0.067. P-value more than 0.05 (p> 0.05). Conclusion: There is a significant effect of giving Cempaka flower extract on blood MDA levels and aortic foam cells of menopausal wistar rats. There was no significant relationship between blood MDA levels and the number of aortic foam cells.